Dual Signals Electrochemical Biosensor for Point‐of‐Care Testing of Amino Acids Enantiomers. Issue 2 (9th August 2021) - Ning, Guyang; Wang, Haiyang; Fu, Mingxuan; Liu, Jiaxian; Sun, Yuena; Lu, Haijun; Fan, Xinyu; Zhang, Yufan; Wang, Huan
Abstract: A highly sensitive electrochemical sensor based on both potential and current dual signals was constructed via polypyrrole‐coated chiral carbon nanotubes (L/D‐CNT@PPy) loaded with Pt nanoparticles (Pt NPs) and β‐cyclodextrin (β‐CD) hybrid. Using L/D‐CNT and β‐CD as chiral selectors, PPy and Pt NPs enhanced the conductivity and the sensors showed excellent performance for chiral recognition of tyrosine (Tyr) and tryptophan (Trp). The linear ranges of the D‐CNT@PPy@Pt NPs@β‐CD sensor were 3–30 μM (Tyr) and 19.6–196 μM (Trp), respectively, the detection limits were 0.107 nM (Tyr) and 0.133 nM (Trp), respectively, and the recoveries for L‐Tyr were 96.56 %–106.32 %. This electrochemical sensor based on a dual‐signal strategy of potential and current was expected to be used in the field of point of care testing (POCT). Abstract :